Effect of the electronic structure on the electrical resistivity of Indium-Lead and Indium-Thallium diluted alloys - Luiggi, Ney José; Gómez, Marisol (Ciencia, 1970)
The incidence of different approaches to the Fermi surface of pure indium, indium-thallium and indium-lead diluted alloys on the residual electrical resistivity has been evaluated in the pseudopotential model. Fermi surface, iterative transport relaxation time and correlated parameters are evaluated in the 8-OPW scheme and all transport integrals are numerically executed using the method of finite elements. The modified Heine-Animalu- Abarenkov scattering potential was used. The particular effects of the scattering of the conduction electrons on the second-zone hole and the third-zone electron β-arm for each Fermi surface (FS) considered were tested, the contribution of the scattering in the second-zone being dominant over other contributions. Our results are in agreement with the experimental ones when the relativistic FS approach is used.